Rights guarantees for people with special needs in higher education institutions - Mohamed, Abeer Hamdy (Journal of Economic, Administrative and Legal Sciences, 2021)
God equals the Almighty and His righteous in his place and did not differentiate between a healthy person and another disabled person. The international community also cared about human rights, and this became very clear in what was endorsed by the Universal Declaration of Human Rights issued by the United Nations in 1948, but the interest came in general and overall and did not address people with special needs directly. With the increase in people with special needs, international societies have to take special care of them, especially as their numbers increase, and attention to their rights has become a special consideration and legal guarantees that protect their rights that have not yet reached a great degree. This prompted me to address the guarantees and rights of people with special needs in higher education institutions.